IgG4-related disease presenting with retroperitoneal fibrosis and hypertrophic spinal pachymeningitis: a rare case report and literature review - Wang, Jianchun; Xu, Feifan; Duan, Hongzhou; Zhao, Juan; Zhang, Haoze; Ren, Jingru; Niu, Zhenyu; Gao, Feng; Chen, Siwei; Liu, Ran (Frontiers in Immunology, 2025)
BackgroundHypertrophic spinal pachymeningitis (HSP) and retroperitoneal fibrosis (RPF) are rare inflammatory disorders, often associated with immunoglobulin G4-related disease (IgG4-RD). This case underscores the diagnostic intricacies and therapeutic challenges in a patient with overlapping neurological and systemic manifestations.Case presentationA 34-year-old female presented with concurrent RPF and HSP leading to urinary tract obstruction and progressive spinal cord compression. The patient initially presented with lower limb weakness and urinary dysfunction, followed by acute paraparesis after a fall. Despite normal serum IgG4 levels, a pathological examination of the dural biopsy confirmed the diagnosis of IgG4-RD. Following a multidisciplinary treatment approach that included surgical decompression, glucocorticoids, immunomodulators and antifibrotic therapy, the patient achieved a favorable clinical outcome.Literature reviewA systematic review of 22 cases involving patients with HSP revealed that key manifestations included localized pain, motor deficits, sensory abnormalities and autonomic dysfunction. The majority of patients (82%, 18/22) exhibited isolated HSP, with a predominance of thoracic spine involvement. Pathological examination demonstrated lymphoplasmacytic infiltration in all cases (100%, 22/22), with 95% (19/20) meeting the criteria for IgG4-positive plasma cells; storiform fibrosis and obliterative phlebitis were observed in 56% (5/9) of cases. Treatment strategies primarily involved surgical decompression (95%, 21/22) and glucocorticoids (95%, 21/22), with 52% (11/21) receiving additional immunosuppressive agents. Clinical outcomes showed complete neurological recovery in 19% (4/21), partial recovery in 71% (15/21). Recurrence was documented in 17% (3/18) of patients with available follow-up data.ConclusionThis rare case underscores the importance of integrating clinical, radiological, and histopathological findings to diagnose HSP and RPF, particularly in the context of IgG4-RD. Early multidisciplinary management is critical to improving outcomes.